2014
DOI: 10.1111/jce.12430
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Epicardial Activation Mapping to Optimize the Site for Video‐Thoracoscopic Left Ventricular Lead Implant

Abstract: Optimization of Left Ventricular Lead PositionBackgroundThe left ventricular (LV) lead local electrogram (EGM) delay from the beginning of the QRS complex (QLV) is considered a strong predictor of response to cardiac resynchronization therapy. We have developed a method for fast epicardial QLV mapping during video-thoracoscopic surgery to guide LV lead placement.MethodsA three-port, video-thoracoscopic approach was used for LV free wall epicardial mapping and lead implantation. A decapolar electrophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have been published on the VAT technique . We showed that the VAT approach is safe and effective.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies have been published on the VAT technique . We showed that the VAT approach is safe and effective.…”
Section: Discussionmentioning
confidence: 58%
“…19 Previous studies have been published on the VAT technique. [19][20][21]24,[28][29][30][31][32][33][34][35][36] We showed that the VAT approach is safe and effective. We included both patients who had undergone unsuccessful de novo transvenous LV lead implantation and patients who had…”
Section: Discussionmentioning
confidence: 73%
“…Since transvenous LV lead reimplantation is frequently not feasible because of the anatomy of the coronary sinus and its tributaries, the benefits and risks of a surgical procedure should be considered. 18 We have recently developed a simple technique of thoracoscopic epicardial mapping during LV lead implantation, 19 which seems safe and efficacious for improvement of LV lead electric position. Whether such an intervention should be performed and when-that is, either early after suboptimum transvenous LV lead implant in all patients or reserved for those with subsequent absence of clinical and echocardiographic response to CRT-remains to be established in future prospective studies.…”
Section: Study Implicationsmentioning
confidence: 99%
“…2 In this regard, the literature shows robotic videothoracoscopic epicardial QLV mapping using a duodecapolar catheter to be highly successful in identifying the optimal LV pacing site using QLV which mirrors our findings. 3 In addition, the use of 3D-EAM serves to provide real-time QLV mapping at the time of surgery thereby offering enhanced precision for optimal LV lead positioning. WEY ET AL.…”
Section: Discussionmentioning
confidence: 99%